A Development Pengembangan Modul Praktikum Kimia Berbasis Proyek pada Materi Larutan Penyangga - Muliati, Eka; Al Idrus, Syarifa Wahidah; Muntari, Muntari (Chemistry Education Practice, 2024)
This research is a study in Research and Development (R&D) that aims to assess the validity and feasibility of project-based chemistry practicum modules. The study adopts a 4D model (define, design, develop, and disseminate). The test subjects in this investigation comprised 21 students from class XII MIPA 1 at SMAN 7 Mataram, selected based on interviews with chemistry teachers. The results indicated that the validity value obtained from the three validators using the Aiken index was V=0.84, signifying that the practicum module was highly valid, and the reliability level was 0.93, indicating that the module is feasible for use. Additionally, the feasibility value of the module demonstrates an average feasibility of 84%, suggesting its high feasibility. Consequently, it can be concluded that the project-based chemistry practicum module developed is highly valid and feasible for use in chemistry learning.